Trace element and OH content of quartz grains in the Amazon river: Potential application in provenance analysis - R. Stalder; D. Jaeger; S. Andò; E. Garzanti; C.M. Chiessi; A.O. Sawakuchi; T. Ludwig; M. Strasser (Sedimentary Geology, 2025)

Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

Behavioral response of three subterranean pests (Agriotes lineatus, Diabrotica virgifera virgifera, Phyllopertha horticola) to the fungal volatile organic compounds 1-octen-3-ol and 3-octanone - Pierre-Antoine Bourdon; Maria Zottele; Zeeshan Zafar; Ian Baxter; Audun Midthassel; Arben Myrta; Katharina F. Wechselberger; Hermann Strasser; Tariq M. Butt (Arthropod-Plant Interactions, 2023)
The volatile organic compounds (VOCs) 1-octen-3-ol and 3-octanone produced by the entomopathogenic fungus Metarhizium brunneum are known to have pesticidal properties at high doses against a range of invertebrate pests. Very little is known about their behavior-modifying (semiochemical) properties. This study focused on investigating the behavioral responses of three subterranean crop pests, wireworm ( Agriotes lineatus ) , western corn rootworm ( Diabrotica virgifera virgifera ), and garden chafer ( Phyllopertha horticola ), to relatively low doses of 1-octen-3-ol and 3-octanone. The behavior of wireworms and corn rootworms were slightly influenced by the VOCs, yet not significantly. Western corn rootworms appeared to be slightly attracted by 100 µl and 200 µl 1-octen-3-ol and 100 µl dose of 3-octanone, respectively but slightly repelled by the higher dose of 3-octanone. Wireworms appeared to be slightly repelled by 1-octen-3-ol and high dose 3-octanone, but slightly attracted by the 100 µl dose of 3-octanone. The VOCs had no significant impact on garden chafer. In silico studies showed that corn rootworm odorant binding proteins (OBPs) had a strong binding affinity of 1-octen-3-ol and high dose 3-octanone, indicating that these VOCs can be detected and recognized by corn rootworm. OBPs are well conserved between species; thus, wireworm and garden chafer OBPs should also be able to bind with the VOCs. Further trials will be done to confirm that VOCs could be used as semiochemicals. Appropriate formulation of the VOCs should increase their efficacy and prevent rapid dissipation of the VOCs.

The increasing threat to European forests from the invasive foliar pine pathogen, Lecanosticta acicola - K. Tubby; K. Adamčikova; K. Adamson; M. Akiba; I. Barnes; P. Boroń; H. Bragança; T. Bulgakov; N. Burgdorf; P. Capretti; T. Cech; M. Cleary; et al. (Forest Ecology and Management, 2023)

Pseudomonas syringae DC3000 infection increases glucosylated N-glycans in Arabidopsis thaliana - Gernot Beihammer; Andrea Romero-Pérez; Daniel Maresch; Rudolf Figl; Réka Mócsai; Clemens Grünwald-Gruber; Friedrich Altmann; Els J. M. Van Damme; Richard Strasser (Glycoconjugate Journal, 2023)
Studying the interaction between the hemibiotrophic bacterium Pseudomonas syringae pv. tomato DC3000 and Arabidopsis thaliana has shed light onto the various forms of mechanisms plants use to defend themselves against pathogen attack. While a lot of emphasis has been put on investigating changes in protein expression in infected plants, only little information is available on the effect infection plays on the plants N-glycan composition. To close this gap in knowledge, total N-glycans were enriched from P. syringae DC3000-infected and mock treated Arabidopsis seedlings and analyzed via MALDI-TOF–MS. Additionally, fluorescently labelled N-glycans were quantified via HPLC-FLD. N-glycans from infected plants were overall less processed and displayed increased amounts of oligomannosidic N-glycans. As multiple peaks for certain oligomannosidic glycoforms were detected upon separation via liquid chromatography, a porous graphitic carbon (PGC)-analysis was conducted to separate individual N-glycan isomers. Indeed, multiple different N-glycan isomers with masses of two N-acetylhexosamine residues plus 8, 9 or 10 hexoses were detected in the infected plants which were absent in the mock controls. Treatment with jack bean α-mannosidase resulted in incomplete removal of hexoses from these N-glycans, indicating the presence of glucose residues. This hints at the accumulation of misfolded glycoproteins in the infected plants, likely because of endoplasmic reticulum (ER) stress. In addition, poly-hexose structures susceptible to α-amylase treatment were found in the DC3000-infected plants, indicating alterations in starch metabolism due to the infection process.

Guidelines on reporting treatment conditions for emerging technologies in food processing - Vicente M. Gómez-López; Gianpiero Pataro; Brijesh Tiwari; Mario Gozzi; María Ángela A. Meireles; Shaojin Wang; Buenaventura Guamis; Zhongli Pan; Hosahalli Ramaswamy; Sudhir Sastry; Florent Kuntz; Patrick J. Cullen; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Overloaded! Critical revision and a new conceptual approach for snow indicators in ski tourism - B. Abegg; S. Morin; O. C. Demiroglu; H. François; M. Rothleitner; U. Strasser (International Journal of Biometeorology, 2021)
Indicators are widely used in climate variability and climate change assessments to simplify the tracking of complex processes and phenomena in the state of the environment. Apart from the climatic criteria, the snow indicators in ski tourism have been increasingly extended with elements that relate to the technical, operational, and commercial aspects of ski tourism. These non-natural influencing factors have gained in importance in comparison with the natural environmental conditions but are more difficult to comprehend in time and space, resulting in limited explanatory power of the related indicators when applied for larger/longer scale assessments. We review the existing indicator approaches to derive quantitative measures for the snow conditions in ski areas, to formulate the criteria that the indicators should fulfill, and to provide a list of indicators with their technical specifications which can be used in snow condition assessments for ski tourism. For the use of these indicators, a three-step procedure consisting of definition, application, and interpretation is suggested. We also provide recommendations for the design of indicator-based assessments of climate change effects on ski tourism. Thereby, we highlight the importance of extensive stakeholder involvement to allow for real-world relevance of the achieved results.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

A streamlined approach for the seismic hazard assessment of a new nuclear power plant in the UK - Guillermo Aldama-Bustos; Iain J. Tromans; Fleur Strasser; Graham Garrard; Guy Green; Liz Rivers; John Douglas; Roger M. W. Musson; Simon Hunt; Angeliki Lessi-Cheimariou; Manuela Daví; Colin Robertson (Bulletin of Earthquake Engineering, 2019)

Probabilistic seismic hazard assessment for a new-build nuclear power plant site in the UK - Iain J. Tromans; Guillermo Aldama-Bustos; John Douglas; Angeliki Lessi-Cheimariou; Simon Hunt; Manuela Daví; Roger M. W. Musson; Graham Garrard; Fleur O. Strasser; Colin Robertson (Bulletin of Earthquake Engineering, 2019)

A subaqueous hazard map for earthquake-triggered landslides in Lake Zurich, Switzerland - M. Strupler; L. Danciu; M. Hilbe; K. Kremer; F. S. Anselmetti; M. Strasser; S. Wiemer (Natural Hazards, 2018)

Internal deformation of a muddy gravity flow and its interaction with the seafloor (site C0018 of IODP Expedition 333, Nankai Trough, SE Japan) - J. S. Laberg; M. Strasser; T. M. Alves; S. Gao; K. Kawamura; A. Kopf; G. F. Moore (Landslides, 2017)

Probabilistic stability evaluation and seismic triggering scenarios of submerged slopes in Lake Zurich (Switzerland) - M. Strupler; M. Hilbe; F. S. Anselmetti; A. J. Kopf; T. Fleischmann; M. Strasser (Geo-Marine Letters, 2017)

Experimental in vivo measurements of light emission in plants: a perspective dedicated to David Walker - Hazem M. Kalaji; Vasilij Goltsev; Karolina Bosa; Suleyman I. Allakhverdiev; Reto J. Strasser; Govindjee (Photosynthesis Research, 2012)

A hypothesis of the Senoumi submarine megaslide in Suruga Bay in Japan—based on the undrained dynamic-loading ring shear tests and computer simulation - K. Sassa; B. He; T. Miyagi; M. Strasser; K. Konagai; M. Ostric; H. Setiawan; K. Takara; O. Nagai; Y. Yamashiki; S. Tutumi (Landslides, 2012)

Contributions of high- and low-quality patches to a metapopulation with stochastic disturbance - Carly A. Strasser; Michael G. Neubert; Hal Caswell; Christine M. Hunter (Theoretical Ecology, 2012)

A strong-motion database from the Central American subduction zone - Maria Cristina Arango; Fleur O. Strasser; Julian J. Bommer; Douglas A. Hernández; Jose M. Cepeda (Journal of Seismology, 2011)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Foodborne outbreak of hepatitis A, November 2007–January 2008, Austria - D. Schmid; R. Fretz; G. Buchner; C. König; H. Perner; R. Sollak; A. Tratter; M. Hell; M. Maass; M. Strasser; F. Allerberger (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Response of plants to ectomycorrhizae in N-limited conditions: which factors determine its variation? - A. Corrêa; R. J. Strasser; M. A. Martins-Loução (Mycorrhiza, 2008)

Receptor-independent sensitization of the adenylyl cylase after chronic treatment with cyclosporine A - G. Simonis; T. Christ; S. K. Bährle; M. Pena; S. P. Schoen; R. Marquetant; U. Ravens; R. H. Strasser (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

JIP test for fast fluorescence transients as a rapid and sensitive technique in assessing the effectiveness of arbuscular mycorrhizal fungi in Zea mays : Analysis of chlorophyll a fluorescence - M. K. Rai; S. Shende; R. J. Strasser (Plant Biosystems, 2008)

The double-resistance-breaking Tomato mosaic virus strain ToMV1-2 contains two independent single resistance-breaking domains - M. Strasser; A. J. P. Pfitzner (Archives of Virology, 2007)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Analysis of mechanisms contributing to AraC-mediated chemoresistance and re-establishment of drug sensitivity by the novel heterodinucleoside phosphate 5-FdUrd-araC - S. Maier; S. Strasser; P. Saiko; C. Leisser; S. Sasgary; M. Grusch; S. Madlener; Y. Bader; J. Hartmann; H. Schott; R. M. Mader; T. Szekeres; et al. (Apoptosis, 2006)

Are Mycorrhiza Always Beneficial? - A. Corrêa; R. J. Strasser; M. A. Martins-Loução (Plant and Soil, 2006)

Influence of histamine release on postoperative vomiting (POV) following gynaecological laparoscopic surgery - K. Kimura; D. Rsch; C. Strasser; M. Lengkong; H. Wulf; M. Koller; I. Celik (Inflammation Research, 2004)

Regulation of protein kinase C isozymes in volume overload cardiac hypertrophy - Martin U. Braun; Paul LaRosée; Gregor Simonis; Mathias M. Borst; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2004)

Metarhizium anisopliae, a potential agent for the control of grape phylloxera - M. Kirchmair; L. Huber; M. Porten; J. Rainer; H. Strasser (BioControl, 2004)

Molecular cloning of cDNA encoding N-acetylglucosaminyltransferase II from Arabidopsis thaliana - R. Strasser; H. Steinkellner; M. Borén; F. Altmann; L. Mach; J. Glössl; J. Mucha (Glycoconjugate Journal, 1999)

Settlement cues in successive developmental stages of the ghost shrimps Callichirus major and C. islagrande (Crustacea: Decapoda: Thalassinidea) - K. M. Strasser; D. L. Felder (Marine Biology, 1998)

The extracellular matrix in hibernating myocardium - a significant factor causing structural defects and cardiac dysfunction - A. Elässer; M. Schlepper; R. Zimmermann; K.-D. Müller; R. Strasser; W.-P. Klövekorn; J. Schaper (Molecular and Cellular Biochemistry, 1998)

Heterologous protein production in yeast - Gerd Gellissen; Karl Melber; Zbigniew A. Janowicz; Ulrike M. Dahlems; Ulrike Weydemann; Michael Piontek; Alexander W. M. Strasser; Cornelis P. Hollenberg (Antonie van Leeuwenhoek, 1992)